Undergraduate student nurses' self-reported preparedness for practice. Issue 4 (December 2015) - Woods, Cindy; West, Caryn; Mills, Jane; Park, Tanya; Southern, Joanne; Usher, Kim
Summary: Background: Tertiary nurse education programmes aim to produce novice nurses able to meet the Nursing and Midwifery Board of Australia competency standards for registration. On the other hand, employers expect graduate nurses to not only be competent and able to function safely and independently but also to be ready to "hit the ground running" in relation to providing clinical care. Aims: The study aimed to explore the perceptions of third-year nursing students enrolled in their final semester with regard to their preparedness for practice. Method: Following their last clinical placement, all third-year nursing students at a regional northern Australian university were emailed a link to an online version of the Casey-Fink Readiness for Practice Survey tool and invited to participate in the study. A total of 113 questionnaires were completed from the sample of 235, giving a response rate of 48%. Results: The majority of students reported feeling prepared for practice and felt that simulation experiences were helpful in attaining this state. Confidence in caring for multiple patients was inversely associated with age indicating higher levels of confidence in younger nursing students. Expanded placements, increased use of simulation for clinical skills practice, smaller clinical skills class sizes and modern equipment were identified as areas for improvement to facilitate and enhance students' levels of confidence and readiness for practice. Conclusions: Students in this study highly valued clinical placements as a method of increasing their levels of perceived preparedness to practice independently after graduation. Caring for multiple patients involves a high level of complexity and a learning curve is indicated in which confidence and competence is likely to grow with experience.